Infeksi Virus Dengue pada Nyamuk Aedes aegypti Menggunakan Artificial Blood Feeding dan Deteksi Virus Dengue Menggunakan Teknik Molekular - Endang Srimurni Kusmintarsih; Medina Fadli Latus Syaadah; Edy Riwidiharso; R Tedjo Sasmono (ASPIRATOR - Journal of Vector-borne Disease Studies, 2019)
Abstract. Artificial blood-feeding using the parafilm-M membrane can be used as an alternative solution andsubstitute live animals as a source of blood. This method is not only be used for blood-feeding but also to infectthe dengue virus (DENV) to mosquitoes. This study was aimed to determine the effectiveness artificial bloodfeeding using parafilm-M membrane in Aedes mosquitoes originated in Indonesia and determine the positivityof mosquitoes infected by Indonesia DENV-1. DENV-1 was isolated from patient and propagated in Vero cellculture. The feeding was done in cardboard cups after mosquitos have been starved for 4-17 hours before beingfed with human blood. A conical 50ml tube was prepared, and a hole was created in the tube lid. The tubeopening was covered with parafilm. Glycerol was added into conical tube and heated in water bath for an hourat 55oC. A mixture of blood and DENV-1 was made with concentration of 10%. Detection of DENV in bloodfedmosquitos was carried out by using Simplexa Dengue Real-Time RT-PCR assay. The results showed thatthe prevalence of blood-fed mosquitoes reached 66.67% with fasting period for 17 hours. Blood feedingmosquitoes are affected by duration of fasting period, blood-feeding time, and attractants from human skinrubbed into parafilm-M membrane. The prevalence of blood-fed Ae. aegypti infected by DENV was 20.83%.This study provides information on the effectiveness of artificial parafilm membrane blood-feeding in alaboratory setting that will be useful for vector control study in Indonesia.